Clinical utility of the 'Determine HBsAg' Point-of-Care Test for Diagnosis of Hepatitis B Surface Antigen in Africa. (4th May 2022) - Ceesay, Amie; Lemoine, Maud; Cohen, Damien; Chemin, Isabelle; Ndow, Gibril
ABSTRACT: Introduction: Chronic infection with hepatitis B virus (HBV) is a leading cause of morbidity and death, especially in sub-Saharan Africa (SSA), where approximately 60 million adults are infected. More than 90% of these patients are unaware of their HBV status. Areas covered: Scaling-up of HBV screening programs in SSA are essential to increase diagnosis, linkage to care, and access to treatment, and will ultimately reduce HBV disease burden to achieve WHO hepatitis elimination targets. Such scale up will rely on inexpensive rapid point-of-care (POC) tests, especially in remote areas where gold standard serological assays are not routinely available. This review discusses the diagnostic performance and clinical utility of the Determine™ (Abbott, USA) hepatitis B surface Antigen (HBsAg) POC test for improving HBV screening in SSA, in light with others available HBsAg rapid tests. Expert Opinion: The Determine™ HBsAg POC test has demonstrated relatively good diagnostic accuracy at the low cost, in the African field and laboratory and should be used for large scale mass screening of HBV infection in Africa.